Atlas of Elastosonography : Clinical Applications with Imaging Correlations - Clevert, Dirk-André; D'Onofrio, Mirko; Quaia, Emilio (Springer International Publishing : Imprint: Springer, 2017)
With the aid of an extensive series of high-quality images, this atlas describes all the potential applications of elastosonography in routine clinical practice. After a brief introduction on technical and physical aspects, the diagnostic benefits of elastosonography in a range of settings are illustrated with the aid of numerous representative cases. The coverage encompasses pathologies of the liver, spleen, pancreas, kidney, breast, thyroid, testis, musculoskeletal system, and vascular system. In addition, helpful correlations with imaging appearances on ultrasound and computed tomography are included. Elastosonography is a powerful, relatively new diagnostic technique that assesses the elasticity of tissues as an indicator of malignancy. Readers will find this book to be an excellent aid to use and interpretation of the technique.
Keywords: Medicine.; Radiology.; elektronické knihy; electronic books